If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(r + 8) = -6 Reorder the terms: -5(8 + r) = -6 (8 * -5 + r * -5) = -6 (-40 + -5r) = -6 Solving -40 + -5r = -6 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + -5r = -6 + 40 Combine like terms: -40 + 40 = 0 0 + -5r = -6 + 40 -5r = -6 + 40 Combine like terms: -6 + 40 = 34 -5r = 34 Divide each side by '-5'. r = -6.8 Simplifying r = -6.8
| 4x-4y+7=15 | | 12x^2-48x=27 | | 4.5x-3=3.5x | | 2x+14=4x-13 | | 5z-5-3z+3=0 | | 35+3a=26 | | 2y=8x-14 | | x^2-11x-5.75=0 | | 5y-25x=50 | | 12+4a=2a | | (7x+5y)(2x-3y)= | | 8*1+y=1 | | 2a+5b-c=4forb | | -11-7x=1023 | | 8*0+y=1 | | 187-3x=42x+22 | | -2(w+8)-(5w-6)=-8w | | 0.12-0.01(x+2)=0.02(4-x) | | 6x+8=-83-7 | | 5x+5=-5-10x | | 5x-5=-55-10x | | 7b^2+2b^2+3= | | 3a-4b=60 | | 0.015(x+30)=1.2 | | 14-9x=50-30x | | -89-7=8x+16 | | 4x^2-29x+13=-9x+4 | | 45=3x-2(20-x) | | 2a(a-1)=3a+3 | | x^2+2-15= | | 7(x+3)+1=2x+5(4+x) | | 4x^2-29x+13=0 |